Studi Empiris tentang Pengaruh Budaya Organisasi, Gaya kepemimpinan, Motivasi Belajar dan Manajemen Pembelajaran terhadap Kinerja Akademik Mahasiswa pada Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto - Vialinda Siswati (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Departing from the analysis of academic social symptoms, the background lack of interest or become a big burden for students to be active in learning due to various orientations including many tasks that are too difficult in quantity and quality. This problem has an impact on student achievement. The low level of student achievement can be seen from the students' achievement and the worse the students postponed the obligation to apply or complete other academic tasks as a whole. This study aims to determine the influence of Organizational Culture, Leadership Style, Motivation learning, And Satisfaction academic service Against Student Academic Performance. This research was conducted at Tarbiyah High School of Raden Wijaya Mojokerto. The number of samples taken 48 students. This study used a saturated sample. Data were collected by survey method. Data analysis technique used is Multiple Linear Regression. The results of this study indicate that organizational culture, leadership style, learning motivation does not affect student academic performance. While learning management have an effect on to student academic performance.